Pharmacognostic Study of Ehretia acuminata R.Br. - Hikmat Ullah Jan; Anis Saeed; Gulnaz Parveen; Naila Mukhtar; Muhammad Siraj; Zulqarnain; Amtul Sami; Muhammad Tayyab Gul (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Ehretia acuminata, commonly known as “Puna” in Pakistan, is from the Boraginaceae family and is used in ecological, medicinal, and agricultural sectors. The current study was conducted to assess the pharmacognostic potency of bark extracts from E. acuminata. The crude distilled water, ethanol, and chloroform extracts signified a concentration-dependent increase in intestinal mobility of the experimented animal, and the plant delivered methodical proof for its pharmacological usage as an antispasmodic drug. The bark distilled water, bark ethanol, and bark chloroform extracts revealed antispasmodic potential (11±1, 9±1, and 11±1) at 300 mg/kg. The distilled water, ethanol, and chloroform extracts also showed analgesic and muscle relaxant potential in the present study and the results were concentration dependent. The bark distilled water, bark ethanol, and bark chloroform extracts revealed the analgesic potential (10±1,16±1, and 11±1) at 300 mg/kg. The Bark distilled water, Bark ethanol, and Bark chloroform extracts revealed the muscle relaxant potential (6±1, 5±1, and 5±1) at 300 mg/kg. While the distilled water, ethanol and chloroform extracts did not show acute toxic effects against the tested animal mice. In this study, bark extracts of E. acuminata showed pharmacological potency in experimental animals. The plant delivered scientific proof for its pharmacological usage as an antispasmodic, acutely toxic, muscle relaxant, as well as an analgesic drug.